Adsorption of Procion Red on Natural Bentonite : Kinetic Studies - Tarmizi Taher; Aldes Lesbani (Sriwijaya Journal of Environment, 2016)
Abstract: Adsorption of procion red on natural bentonite was studied by kinetic study to know the reactivity of procion red. Kinetic adsorption was determined using batch adsorption system at various times in several concentrations of procion red. Time of adsorption was investigated at 5, 10, 20, 30, 45, 60, 90, and 120 minutes in 10, 25, 50, and 75 mg/L of procion red. The data was calculated using Langmuir-Hinshelwood kinetic equation. The diffusions process of procion red into bentonite at lower concentration was faster than at higher concentration in general with fit correlation between [(ln(Co/C))/C] vs t/C from Langmuir-Hinshelwood data. The adsorption procion red on bentonite data at various times shows Langmuir monolayer adsorption process in the surface of bentonite.Keyword: adsorption, procion red, natural bentonite, kineticAbstrak (Indonesian): Adsorpsi procion merah pada bentonit alam telah dipelajari melalui studi kinetik untuk mengetahui reaktivitas procion merah. Kinetika adsorpsi ditentukan menggunakan sistem adsorpsi simultan pada berbagai waktu dalam beberapa konsentrasi procion merah. Waktu adsorpsi dipelajari pada 5, 10, 20, 30, 45, 60, 90, dan 120 menit pada konsentrasi procion merah 10, 25, 50, dan 75 mg/L. Data dihitung menggunakan persamaan kinetika Langmuir-Hinshelwood. Proses difusi procion merah ke dalam bentonit pada konsentrasi rendah lebih cepat dibanding pada konsentrasi lebih tinggi secara umum dengan hubungan korelasi yang lurus antara [(ln(Co/C))/C] versus t/C dari data Langmuir-Hinshelwood. Adsorpsi procion merah pada bentonit dengan berbagai variasi waktu adsorpsi menunjukkan proses adsorpsi satu lapisan pada permukaan bentonit. Katakunci: adsorpsi, procion merah, bentonit alam, kinetik